2013
DOI: 10.1371/journal.pone.0056361
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Carbon Dioxide and Food Odours in Drosophila: Olfactory Hedonics and Sensory Neuron Properties

Abstract: Behavioural responses of animals to volatiles in their environment are generally dependent on context. Most natural odours are mixtures of components that can each induce different behaviours when presented on their own. We have investigated how a complex of two olfactory stimuli is evaluated by Drosophila flies in a free-flying two-trap choice assay and how these stimuli are encoded in olfactory receptor neurons. We first observed that volatiles from apple cider vinegar attracted flies while carbon dioxide (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 59 publications
9
42
3
Order By: Relevance
“…Among vinegar flies, it is known that fruit volatiles are involved in Drosophila spp. orientation (e.g., Lebreton et al 2012, Faucher et al 2013) and oviposition behaviors (e.g., Stensmyr et al 2012, Linz et al 2013. Revadi et al (2012) showed recently that D. suzukii flies are attracted to odors from intact raspberry, blackberry, blueberry, cherry, and strawberry fruit, indicating that fruit volatiles are important in D. suzukii host location.…”
Section: Discussionmentioning
confidence: 99%
“…Among vinegar flies, it is known that fruit volatiles are involved in Drosophila spp. orientation (e.g., Lebreton et al 2012, Faucher et al 2013) and oviposition behaviors (e.g., Stensmyr et al 2012, Linz et al 2013. Revadi et al (2012) showed recently that D. suzukii flies are attracted to odors from intact raspberry, blackberry, blueberry, cherry, and strawberry fruit, indicating that fruit volatiles are important in D. suzukii host location.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, not all food odors and thus potential food sources might inhibit CO 2 avoidance by these means. Certainly, vinegar in spite of its behavioral effect does not fall into this category and does not affect sensory neuron responses to CO 2 [13]. Second, it is likely more efficient to block or modulate a neural pathway at multiple levels.…”
Section: Higher-order Processing Of Conflicting Sensory Informationmentioning
confidence: 99%
“…Despite this positive association, flies innately avoid CO 2 across a large range of concentrations, possibly because it may represent a danger signal released by other flies in stressful situations [9]. How and where flies process CO 2 in these two different contexts to either overcome or submit to their aversion of this odor is not fully understood [10][11][12][13]. Behavioral drive and internal state, however, appear to strongly impact on how CO 2 is perceived [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses were calculated as the mean distance flies covered within 4 s after encounter with the odour pulse. In the free-flight trap assay, 30, 4-6 day old female flies, starved for 24 h were released in a 50×50×50 cm mesh cage (Faucher et al, 2013). From preliminary tests, fly catches using either vinegar alone or the single odour were low when tested in the free-flight assay.…”
Section: Behavioural Assaysmentioning
confidence: 99%